2020
DOI: 10.1016/j.jallcom.2019.153343
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the iron-nitrogen system with vacancies. From first principles to applications

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…There is evidence that this distinction between DFT and iron alloys in reality is significant when making thermodynamic predictions from first principles. For example, it has been shown that DFT-calculated nitrogen solubility's in iron have closer agreement with experimental data when excess vacancies [3] are introduced to idealised lattices. Furthermore, common processes encountered in industry; such as irradiation [4,5], quenching [6], ball milling and shot peening [7]; lead to deformed lattices which further increase nitrogen-vacancy interactions.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…There is evidence that this distinction between DFT and iron alloys in reality is significant when making thermodynamic predictions from first principles. For example, it has been shown that DFT-calculated nitrogen solubility's in iron have closer agreement with experimental data when excess vacancies [3] are introduced to idealised lattices. Furthermore, common processes encountered in industry; such as irradiation [4,5], quenching [6], ball milling and shot peening [7]; lead to deformed lattices which further increase nitrogen-vacancy interactions.…”
Section: Introductionmentioning
confidence: 80%
“…First principles data calculated as outlined in section 2.1 is used in combination with published data from [3] to calculate the jump rates for diffusion (see section 2.2.1) in BCC/FCC iron containing vacant lattice sites and interstitially dissolved nitrogen. Section 2.1 features only new/essential details regarding the DFT methodology applied, the reader is referred to the previously published work mentioned for more detailed discussion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of the equilibrium in the Fe-N system allows obtaining information regarding the phase composition of the nitrided layers obtained under strict conditions of temperature and nitrogen concentration in the furnace chamber atmosphere [ 1 , 2 , 3 , 4 , 5 ]. The adjustment of the nitrided layer phase composition can be set by altering the nitrogen potential of the atmospheres used: by maintaining it at the level of nitrogen solubility in a certain phase, one is able to control the phase composition of the layer [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%